2018
DOI: 10.1101/gad.313973.118
|View full text |Cite
|
Sign up to set email alerts
|

NDF, a nucleosome-destabilizing factor that facilitates transcription through nucleosomes

Abstract: Our understanding of transcription by RNA polymerase II (Pol II) is limited by our knowledge of the factors that mediate this critically important process. Here we describe the identification of NDF, a nucleosome-destabilizing factor that facilitates Pol II transcription in chromatin. NDF has a PWWP motif, interacts with nucleosomes near the dyad, destabilizes nucleosomes in an ATP-independent manner, and facilitates transcription by Pol II through nucleosomes in a purified and defined transcription system as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 50 publications
0
42
1
Order By: Relevance
“…Furthermore, GLYR1 downregulation was also found to reduce the sensitivity of CRC cells to 5-FU. However, Fei et al reported that GLYR1 knockout prolonged the G1 phase and inhibited growth of HeLa cells [55], which was contrary to our results. This discrepancy may be because of the different cell lines used in our study and the function of GLYR1 may be influenced by the heterogeneity of tumors.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, GLYR1 downregulation was also found to reduce the sensitivity of CRC cells to 5-FU. However, Fei et al reported that GLYR1 knockout prolonged the G1 phase and inhibited growth of HeLa cells [55], which was contrary to our results. This discrepancy may be because of the different cell lines used in our study and the function of GLYR1 may be influenced by the heterogeneity of tumors.…”
Section: Discussioncontrasting
confidence: 99%
“…First, we designed nucleosome substrates with linker DNA ends blocked by two different end-blocking strategies: the Lac repressor R3 system and the streptavidin-biotin system. Finally, to further test whether Rhp26 is able to disassemble nucleosomes from the nucleosomal array, we used a nucleosome array with a circular plasmid (42). We obtained similar results from all three systems, which are summarized below.…”
Section: Distinct Functions Of Rhp26 C-terminal Region a And Region Bmentioning
confidence: 70%
“…To further test whether Rhp26 is able to disassemble nucleosomes from the nucleosome array, we assembled chromatin on circular DNA using a salt dialysis method and then tested Rhp26's effect on the topology of DNA supercoiling in the nucleosome (42). In the presence of ATP, but not UTP, treatment with the active form of Rhp26 17-910 and topoisomerase I (Topo I) decreased the superhelicity of nucleosomal structures on plasmid DNA in a dose-dependent manner ( Fig.…”
Section: Distinct Functions Of Rhp26 C-terminal Region a And Region Bmentioning
confidence: 99%
“…NDF (nucleosome destabilizing factor) which was found associated with JIL-1 by mass spectrometry after cross-linking 50 was also enriched (Fig.7a). NDF has recently been shown to destabilize nucleosomes in front of the transcribing polymerase, but its depletion had only minor effects on overall transcript levels 51 . We speculated that the JJ-complex and NDF may have redundant functions on transcription.…”
Section: Resultsmentioning
confidence: 99%